PEMODELAN DAN ANALISIS SEBARAN RADIONUKLIDA DARI PWR PADA KONDISI ABNORMAL DI TAPAK BOJANEGARA-SERANG - Kuntjoro, Sri (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
Additional of electrical power especially Nuclear Power Plant will give radiological consequences to population and environment due to radioactive release in normal and abnormal condition. In consequence the management of nuclear power plant must supply data and strong argumentation to clarify the safety of nuclear power plant to environment. For that purpose it needs to be carried out an analysis of abnormal condition in nuclear power plant and its radiological consequences to the environment. That analysis is done using abnormal condition simulation model postulated on 1000 MWe nuclear power plant. That simulation model is used also to evaluate environmental potential as site capability in supporting the radiological consequences. Radionuclide transport modeling from reactor core to containment uses EMERALD computer code. Other computer codes are Windrose, PC-COSYMA and ArcView are used to simulate meteorology condition, radionuclide release to population distribution of food production and consumption and distribution of radiation dose received to population around nuclear power plant. Application of that simulation is carried out to NPP candidate site in Bojanegara-Kramatwatu, Serang Banten peninsula. Using source term data, meteorology data, dispersion data and pathways modeling are resulting radionuclide dispersion model and radiation pathway acceptance at the surrounding nuclear power plant site (Bojanegara-Serang peninsula). The result shows that maximum radiation dose received is lower than dose permitted in accordance with regulatory body (BAPETEN).